THE ROLE OF BRAND AWARENESS IN MEDIATING THE EFFECT OF SOCIAL MEDIA MARKETING ON PURCHASE DECISIONS - Putu Egayuni; Ni Made Wulandari Kusumadewi (Adisam Publisher, 2026)
This study aims to analyze the effect of social media marketing on purchase decisions, with brand awareness as a mediating variable, at Beauty Shop in Buleleng Regency. The phenomenon of increasing competition in the beauty industry requires business actors to implement effective digital marketing strategies through social media, particularly Instagram. This research employed a quantitative approach using an associative method. The sample consisted of 100 respondents selected through purposive sampling, with the criteria of having made a purchase at Beauty Shop’s Head Branch and actively using social media. Data were collected through a closed-ended questionnaire and analyzed using path analysis with the assistance of SPSS software. The results indicate that social media marketing has a positive and significant effect on purchase decisions as well as on brand awareness. In addition, brand awareness has a positive and significant effect on purchase decisions. Mediation testing shows that brand awareness partially mediates the effect of social media marketing on purchase decisions. These findings demonstrate that the effectiveness of social media marketing strategies influences purchase decisions not only directly but also indirectly through increased consumer brand awareness. This study contributes theoretically by strengthening the Stimulus–Organism–Response (S-O-R) theory and provides practical references for business actors in optimizing digital marketing strategies to enhance sales and consumer loyalty.